Influence of fertilizer types and placement methods on the yield of white yam Dioscorea rotundata - Tajudeen Akinrinola; Peter Babajide (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Yam cultivation in soils of low fertility has been a major cause of yield decline in Nigeria. The inadequacies associated with either inorganic or organic fertilizer in the aspects of crop growth and productivity necessitated the introduction of organomineral fertilizers. However, information on the appropriate placement method for sustainable cultivation is still limited. Hence, fertilizer type and placement method were evaluated on white yam yield.Method: Dioscorea rotundata (Tdr 219) performance under different fertilizer types [NPK, 15-15-15 and organomineral fertilizer (OMF) at 30 kg N/ha], and different methods of placement (Side/spot and Ring/circular placements) were evaluated.Results: The average tuber length, circumference, number of ware tubers, and yam tuber weights were higher under NPK treatment, while the number of tubers was higher in OMF treatment. All parameters observed were increased by ring fertilizer placement method compared to side placement. The interaction of fertilizer type and method of placement indicated that under OMF, the ring placement produced comparatively higher tuber weight (13390.0 kg/ha) than side placement (13166.6 kg/ha). However under NPK fertilizer, side placements enhanced tuber weight (15173.3 kg/ha) compared with ring placement (15076.6 kg/ha). The residual cropping revealed that the highest and significant tuber weight was observed in OMF fertilizer with ring placement compared to the other treatments.Conclusion: Side placement was appropriate for NPK fertilizer, however, applying organomineral fertilizer at 2000 kg/ha with ring placement was recommended for the cultivation of yam in low fertility soils.